2017
DOI: 10.1111/php.12717
|View full text |Cite
|
Sign up to set email alerts
|

UVA Light‐mediated Ascorbate Oxidation in Human Lenses

Abstract: Whether ascorbate oxidation is promoted by UVA light in human lenses and whether this process is influenced by age and GSH levels are not known. In this study, we used paired lenses from human donors. One lens of each pair was exposed to UVA light whereas the other lens was kept in the dark for the same period of time as the control. Using LC-MS/MS analyses, we found that older lenses (41 to 73 years) were more susceptible to UVA-induced ascorbate oxidation than younger lenses (18 to 40 years). Approximately 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Salo et al [ 8 ] found that UVA is required for a range of functions in animal creatures, including as a powerful modulator of fish immune defense. Rakete et al [ 9 ] reported that UVA led to protein aggregation through ascorbate oxidation in humans. Additionally, according to previous research in our laboratory, the full spectrum plus a UVA light environment was most conducive to the development of P. vannamei [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salo et al [ 8 ] found that UVA is required for a range of functions in animal creatures, including as a powerful modulator of fish immune defense. Rakete et al [ 9 ] reported that UVA led to protein aggregation through ascorbate oxidation in humans. Additionally, according to previous research in our laboratory, the full spectrum plus a UVA light environment was most conducive to the development of P. vannamei [ 10 ].…”
Section: Introductionmentioning
confidence: 99%